2018
DOI: 10.4236/wjcd.2018.81008
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Cardiovascular Diseases as Seen in an Out-Patient Cardiac Clinic in Ghana

Abstract: Cardiovascular diseases (CVDs) are increasingly emerging as a major health problem in sub-Saharan Africa, but information on the epidemiology, clinical characteristics and spectrum of the diseases are scanty. Epidemiological data regarding the incidence and prevalence of CVDs in different geographical regions are essential to our understanding of global distribution and evolution of CVDs. We conducted a retrospective observational study to determine the prevalence and spectrum of cardiovascular diseases in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Rheumatic heart disease has mostly disappeared in most industrialized nations, but it remains a significant clinical and public health issue in Ghana and several other developing countries. 1,13,18,19 The clinical and socio-demographic profile of patients with RHD attending the adult cardiac clinic of the Komfo Anokye Teaching Hospital in Kumasi, Ghana, is described in this study. A total of 140 individuals (37 men and 103 women) were investigated retrospectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rheumatic heart disease has mostly disappeared in most industrialized nations, but it remains a significant clinical and public health issue in Ghana and several other developing countries. 1,13,18,19 The clinical and socio-demographic profile of patients with RHD attending the adult cardiac clinic of the Komfo Anokye Teaching Hospital in Kumasi, Ghana, is described in this study. A total of 140 individuals (37 men and 103 women) were investigated retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations, however, have found that mitral regurgitation with mitral stenosis is the most prevalent valvular presentation in RHD. 13,23 Mitral stenosis is the most prevalent valvular lesion in RHD, according to a few studies. 31 Surprisingly, there was no evidence of mitral stenosis in this report.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac diseases have also been identified as a major non-communicable disease among children in SSA [ 13 ]. Several authors such as BeLue et al [ 9 ], Monti et al [ 14 ], Amegah [ 12 ], van der Sande [ 15 ], Yach et al [ 16 ], Tokoudagba et al [ 17 ], Nkoke and Luchuo [ 18 ], and Owusu and Acheamfour-Akowuah [ 19 ], among others, have attributed the increase in the burden of CVDs and related risk factors in the region to certain agents. These include the epidemiological transition brought about by increasing urbanization, changing lifestyle/dietary patterns, socioeconomic development, and modernization.…”
Section: Introductionmentioning
confidence: 99%
“…They include heart failure (also referred to as congestive heart failure), stroke, coronary artery, coronary heart, cerebrovascular, and rheumatic heart diseases [ 1 , 6 , 21 , 22 ], as well as other conditions, with diabetes, hypertension, high cholesterol/hyperlipidemia, obesity (abnormal or excessive fat accumulation), tobacco/cigarettes use, increase in age, sedentary lifestyle, and genetic predisposition, among others, as risk factors [ 2 , 3 , 7 , 20 , 23 , 24 ]. In SSA countries, the CVDs challenge has given rise to additional pressure on the healthcare systems, which are still struggling to cope with other diseases that affect the region [ 19 ].…”
Section: Introductionmentioning
confidence: 99%